2017
DOI: 10.1049/iet-bmt.2016.0075
|View full text |Cite
|
Sign up to set email alerts
|

Super resolution and recognition of long range captured multi‐frame iris images

Abstract: In this study, a framework to super resolve and recognise the long range captured iris polar images is proposed. The proposed framework consists of best frame selection algorithm, modified diamond search algorithm, Gaussian process regression (GPR) based and enhanced iterated back projection (EIBP)-based super-resolution approach, fuzzy entropy-based feature selector and neural network (NN) classifier. The framework uses linear kernel co-variance function in local patch-based GPR and EIBP algorithms and it sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The CASIA Long Range database has also been used in a number of studies [35], [36]. Deshpande and Patavardhan [35] employed Gaussian Process Regression (GPR) and Enhanced Iterated Back Projection (EIBP) to super-resolve iris images. The best frame was selected as reference for alignment purposes by using the Discrete Cosine Transform.…”
Section: B Reconstruction-based Methods In the Pixel Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…The CASIA Long Range database has also been used in a number of studies [35], [36]. Deshpande and Patavardhan [35] employed Gaussian Process Regression (GPR) and Enhanced Iterated Back Projection (EIBP) to super-resolve iris images. The best frame was selected as reference for alignment purposes by using the Discrete Cosine Transform.…”
Section: B Reconstruction-based Methods In the Pixel Domainmentioning
confidence: 99%
“…The GPR is a time consuming process, therefore patches with less amount of information (measured by their variance of intensity) are processed with the faster EIBP algorithm. Performance was evaluated in [35] by downsampling iris images, and then super-resolving them. The authors reported several image fidelity measures in the pixel domain between original high-quality images and reconstructed images.…”
Section: B Reconstruction-based Methods In the Pixel Domainmentioning
confidence: 99%
“…Other studies have proposed to incorporate quality measures [57,59,63,35], so more weight is given to frames with higher quality [28]. Recent reconstruction-based studies have proposed the use of Gaussian Process Regression (GPR), Enhanced Iterated Back Projection (EIBP) [17], and Total Variation regularization algorithms [16] to super-resolve polar frames.…”
Section: Iris Super-resolutionmentioning
confidence: 99%
“…In [18], Nguyen et al introduce a signal-level fusion to integrate quality scores to the reconstructionbased SR process performing a quality weighted SR for a LR video sequence of a less constrained iris at a distance or on the move obtaining good results. However, in this case, as in [19] that perform the best frame selection, many LR images are required to reconstruct the HR image which is one of the disadvantages of this kind of reconstruction-based methods.…”
Section: Related Workmentioning
confidence: 99%